"Evaluación de la sincronía floral en la producción de semilla en un híbrido triple experimental de maíz (Zea mays L.) en época seca". - Aguayo Macías, Jefferson Roberto (2016)
One of the challenges for plant breeders and seed producers is to obtain the quantity and quality of this, for it have developed different tools and methods to optimize the process of obtaining seed, taking between these methods synchronization in bloom to to get a better filling pollinating grains and performance as a desynchronization makes difficult to maintain the genetic quality due to contamination with foreign pollen. The overall objective was to evaluate different planting dates to synchronize flowering between parental triple hybrid UTEQ to increase seed production, and the specific objectives were to determine the planting season parental to optimize synchronization, set the planting time to produce the highest seed yield of corn and identify the range of sowing the male parent, which produces the largest grain filling. This research was conducted on the grounds of the Experimental Farm "La Maria", owned by the State Technical University of Quevedo, located at Km 7 Quevedo route - El Empalme, Los Rios province, sowing the male parent one day before, the same day, one, two, three and four days after the female parent, using as genetic material experimental hybrid UTEQ. For this purpose a design of randomized complete blocks with six treatments were used, and the statistical difference was established by Tukey test at 95% probability. With floral synchrony 4 (male parent 2 days after the female) fewer days was obtained male flowering with 49.3 days. by sowing the male parent 1 day before the female shortest time appeared to silking with 51.9 days, cobs greater weight with 133.9 grams and higher yield with 5131.9 kg / ha. Sembrando the male parent four days after the female greater number of incomplete grains was observed. The difference between the number of days of male and female flowering ranges from 1.9 for sowing the male parent a day earlier and 3.5 for the floral synchrony 6 (male parent 4 days after the female). Keywords: corn, floral synchrony, parental maize seed